THE INFLUENCE OF REGIONAL TAXES, REGIONAL LEVIES AND REGIONAL COMPANY PROFITS ON ORIGINAL INCOME OF BOJONEGORO DISTRICT GOVERNMENT - Agustina, Putri Ella; Widajantie, Tituk Diah (Yayasan Education and Social Center, 2024)
This research was conducted with the aim of analyzing the influence of Regional Taxes, Regional Levies and Regional Company Profits on Regional Original Income. This type of research is quantitative research with data analysis techniques used, namely multiple linear regression analysis and hypothesis testing using the SPSS Version 26 software program. This research uses secondary data sourced from the District Regional Revenue Agency. Bojonegoro with time series data collection over a period of five years, namely 2018 to 2022. The method for determining the sample in this research is purposive sampling. The results of this research are that local taxes have no effect on local original income; regional levies influence regional original income; and the regional company profit variable has an effect on regional original income. It can be concluded that this research highlights that in the observed situation, the contribution of regional taxes, regional levies and regional company profits to the regional original income variable cannot be considered as the main factor, but further analysis is needed to understand the context and other variables that may influence the relationship between regional taxes, regional levies, regional company profits, and regional original income